PENERAPAN METODE DRILLING MENGGUNAKAN GOOGLE FORMS UNTUK MENINGKATKAN KEMAMPUAN MENULIS LAFAZ DAN MENERJEMAHKAN SURAH AL-FATIHAH PADA SISWA KELAS VII MTS NURUL HAQ BALARAJA KABUPATEN TANGERANG - Siti Umroh; Agus Santoso (LPSDI Bina Patria, 2024)
Surah Al-Fatihah, which is the opening Surah in the Qur’an, is often read during a prayer and it will be more solemn if you understand its meaning because for a Muslim, it is not said to be praying if he does not read the Surah. However, only six of the 36 students managed to write and translate Surah Al-Fatihah. To solve the problem, the Drilling Method was implemented by applying Google Forms in the teaching-learning activities where the recitation of Surah Al-Fatihah was repeated and increased for those who had not completed it. The Classroom Action Research was used, consisting of three cycles involving the 36 students of the Class VII MTS Nurul Haq Balaraja. The data were obtained through the tests using the Student Worksheets, Google Forms, observations, interviews, activity photos and field notes. The results have indicated that the application of the Drilling Method can improve the students’ abilities in the Reading and Writing Al-Qur'an class.